Pengamatan Morfologi Bagian Tanaman Lima Kultivar Kedelai [Glycine max (L.) Merrill] - Sumarmi, S; Triyono, Kharis (Bioma : Berkala Ilmiah Biologi, 2022)
Written descriptions of soybean plants often have different results after planting. Not much has been done to observe the morphology of the anthers of various soybean cultivars. Not much has been done to observe the morphology of the anthers of various soybean cultivars. This study aims to observe the morphological characteristics of five soybean cultivars.  The research was conducted in the research field and plant laboratory at the Faculty of Agriculture, Universitas  Slamet Riyadi, Surakarta, using a completely randomized design. Five soybean cultivars were planted namely Argomulyo, Grobogan, Wilis, Anjasmoro and Hitam Malika. Observations on the seeds used, plant height growth, leaf morphology, flower morphology and anther conditions. Argomulyo, Grobogan and Anjasmoro cultivars have large seeds, weighing 100 seeds between 15-18 grams. Plant height growth occurs until the plant is 5 weeks old. The color and shape of the leaves of five one-month-old soybean cultivars are almost the same. At the beginning of the 2nd month, the leaves of the soybean plants turned dark green, which was evident in Grobogan and Hitam Malika cultivars. The crown color of the Black Malika soybean flower is dark purple, different from the other 4 cultivars with purple flowers. Cultivar Anjasmoro, 5 weeks old, reached 63 cm, the highest among the five cultivars planted. Each soybean cultivar has morphological characteristics in terms of plant height, shape, leaf color, flowers, pods, seeds and or anthers.